A method for facilitating end-user mashup based on description. (1st January 2014) - Guo, Junxia; Han, Hao
The development of mashup technology has allowed people to more efficiently create web applications with existing information drawn from the web. However, not every mashup developer can use any given web source in a mashup. There are two technological problems. First, it is not always possible to reuse a given source. There are web applications and web services, two kinds of sources. The traditional way of reusing web services is to write a program. Relevant and applicable approaches are needed in order to reuse web applications. Second, it must be possible for users without programming knowledge to reuse an existing web source. In this paper, we propose an effective approach that allows end-users to build mashup applications with almost any part(s) of web applications and REST web services without programming. Our approach supports the more flexible transfer of information between components, which can be achieved via a web application or REST web service.